2014
DOI: 10.1007/s11205-014-0749-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Self-efficacy, Trauma and Well-Being in Emergency Medical Dispatchers

Abstract: Emergency medical dispatchers (EMDs) respond to crisis calls for ambulance; they dispatch paramedics and provide emotional and medical assistance to callers. Despite the stressful nature and exposure to potentially traumatising events in this role, there has been no published research specifically investigating well-being or posttraumatic growth among EMDs. Extrapolating from research conducted among other emergency services workers (e.g., paramedics, police), literature attests to the importance of self effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 40 publications
3
80
1
4
Order By: Relevance
“…For medical crisis, the unseen role of the EMD has historically been seemingly unrecognized both in literature and the public eye. But new research is emerging that shines light on the personal impacts for those who provide the first response remotely in an emergency (Adams, Shakespeare-Finch, & Armstrong, 2014;Shakespeare-Finch, Rees, & Armstrong, 2014).…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…For medical crisis, the unseen role of the EMD has historically been seemingly unrecognized both in literature and the public eye. But new research is emerging that shines light on the personal impacts for those who provide the first response remotely in an emergency (Adams, Shakespeare-Finch, & Armstrong, 2014;Shakespeare-Finch, Rees, & Armstrong, 2014).…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…The researchers reported that older age was associated with higher levels of psychological stress, but that the coping strategy of seeking support from others predicted lower levels of post-traumatic stress in all groups . Receiving social support was related to increases in psychological well-being and post-traumatic growth, and to lower levels of PTSD incidence, in Australian emergency medical dispatchers (Shakespeare-Finch et al 2014). A study of Italian rescue workers found that degree of life satisfaction was associated with the workers' sense of community and collective efficacy (that is, their ability to work collaboratively and effectively) within their organization (Cicognani et al 2009).…”
Section: Relatedness Belonging and The Role Of Social Supportmentioning
confidence: 99%
“…Emergency medical dispatchers can experience vicarious, or secondary, trauma from dealing with stresses such as the need to make urgent decisions about traumatic events and judge situations based on incomplete information (Shakespeare-Finch et al 2014).…”
Section: Perceived Coping Self-efficacy In Studies Involving Emergencmentioning
confidence: 99%
“…Relationships have been found to impact various aspects of both physical and psychological well-being (Brown, Nesse, Vinokur, & Smith, 2003;Caligiuri & Lazarova, 2002;Israel-Cohen, Kaplan, Noy, & Kashy-Rosenbaum, 2016;ShakespeareFinch & Obst, 2011;Shakespeare-Finch, Rees, & Armstrong, 2014).…”
Section: Relationships With Othersmentioning
confidence: 99%
“…Supportive relationships have been shown to help individuals dealing with stressful or difficult situations (Caligiuri & Lazarova, 2002;Israel-Cohen et al, 2016;Shakespeare-Finch et al, 2014). Understanding more about how a missionary's supportive relationships with God and other people can impact missionary adjustment to a new culture may help with the often-stressful adjustment process.…”
Section: Why Study the Questions?mentioning
confidence: 99%